Spontaneous Bacterial Pericarditis and Coronary Sinus Endocarditis Caused by Oxacillin-Susceptible Staphylococcus aureus - Maurício N. Machado; Marcelo A. Nakazone; Isabela T. Takakura; Carolina M. P. D. C. Silva; Lilia N. Maia (Case Reports in Medicine)
This paper describes a case of a 44-year-old male patient previously healthy admitted with an unusual spontaneous acute bacterial pericarditis associated with coronary sinus mass. Two-dimensional echocardiography showed large loculated pericardial effusion with signs of diastolic restriction and an image suggesting vegetation in topography of the right atrium coronary sinus. Pericardial drainage, coronary sinus vegetation resection, and antibiotic therapy with Oxacillin were performed due to Oxacillin-susceptible Staphylococcus aureus identified on the pericardial effusion and blood culture. This is a rare condition and a unique combination of a spontaneous acute bacterial pericarditis with coronary sinus endocarditis without cardiac valve compromise.